Risk of HIV/AIDS Events in Patients at Dr. General Hospital Pirngadi Medan Period 2013- 2017 - Siregar, Robiyatul Adwiyah (Sari Mutiara Indonesia University Press, 2018)
HIV/AIDS is rapidly increasing in Indonesia and can cause death, especially in productive aged people. It is caused by the decrease in immune system due to the infection. The objective of the research was to analyze the risk factors for the incidence of HIV/AIDS in patients at Pirngadi Hospital, medan, in period of 2013-2017. The research used case control design. The population was 939 data of HIV/AIDS inpatients in the period of 2013-2017. The number of samples (case and control)was in the ration of 1:1 (115 cases and 115 controls) so that there were 230 samples all together. The data were gathered by analyzing secondary data from the VCT clinic and medical records of HIV/AIDS patientsin the period of 2013-2017. The gathered data were analyzed by using univariate analysis, bivariate analysis with chi square test, and multivariate analysis with multiple logistic regression analysis. The result of the research showed that there was the correlation of marital status (p=0.004; OR=2.171), free sex (p=0.000; OR=3.218), with the incidence of HIV/AIDS.There was no correlation of age (p=0.377; OR=0.771), with the incidence of HIV/AIDS.The variable which had themost dominant influence was using free sex (p=0.000; OR=3.218)it isrecommended that the patient at pirngadi hospital, medan, increases their attention and understanding as early as possible the risk factors of the incidence of HIV/AIDS so that it can be prevented